Interannual variability (2000–2013) of mesopelagic and bathypelagic particle fluxes in relation to variable sea ice cover in the eastern Fram Strait - Salter, I.; Bauerfeind, E.; Fahl, K.; Iversen, M. H.; Lalande, C.; Ramondenc, S.; Von Appen, W.-J.; Wekerle, C.; Nöthig, E.-M. (Frontiers in Earth Science, 2023)
The Fram Strait connects the Atlantic and Arctic Oceans and is a key conduit for sea ice advected southwards by the Transpolar Drift and northward inflow of warm Atlantic waters. Continued sea ice decline and “Atlantification” are expected to influence pelagic benthic coupling in the Fram Strait, and Arctic as a whole. However, interannual variability and the impact of changing ice conditions on deep water particle fluxes in the Arctic remains poorly characterised. Here we present long term sediment trap records (2000-2013) from mesopelagic (200 m) and bathypelagic (2300 m) depths at two locations (HGIV and HGN) in the Fram Strait subject to variable ice conditions. Sediment trap catchment areas were estimated and combined with remote sensing data and a high resolution model to determine ice cover, chlorophyll concentration and prevailing stratification regimes. Surface chlorophyll increased between 2000-2013, but there was no corresponding increase in POC flux, suggesting a shift in the efficiency of the biological carbon pump. A decrease in particulate biogenic Si (pbSi) flux, %opal, Si:POC and Si:PIC at mesopelagic depths indicate a shift away from diatom-dominated export as a feasible explanation. Biogenic components accounted for 72 ± 16% of mass flux at 200 m, but were reduced to 34 ± 11% at 2300 m, substituted by residual (lithogenic) material. Total mass fluxes of biogenic components, including POC, were higher in the bathypelagic. Biomarkers and ∂13C values suggest lateral advection and ice-rafted material both contribute to benthic carbon input, although constraining their precise contribution remains challenging. The decadal time series was used to describe two end-members of catchment area conditions representing maximum temperatures of Atlantic inflow water in 2005 at HGIV and high ice-coverage and a meltwater stratification regime at HGN (2007). Despite similar chlorophyll concentrations, bathypelagic POC flux, Si flux, Si:POC and Si:PIC were higher and POC:PIC lower in the high ice/meltwater regime. Our findings suggest that ice concentration and associated meltwater regimes causes higher diatom flux. It is possible this will increase in the future Arctic as meltwater regimes increase, but it is likely to be a transient feature that will disappear when no ice remains.